2008
DOI: 10.1021/jf8005068
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effectiveness of Phenolic Apple Juice Extracts and Their Gut Fermentation Products in the Human Colon Carcinoma Cell Line Caco-2

Abstract: Apples represent a major dietary source of antioxidative polyphenols. Their metabolic conversion by the gut microflora might generate products that protect the intestine against oxidative damage. We studied the antioxidant effectiveness of supernatants of fermented apple juice extracts (F-AEs, 6 and 24 h fermentation) and of selected phenolic degradation products, identified by HPLC-DAD-ESI-MS. Cell free antioxidant capacity of unfermented apple juice extracts (AEs) was decreased after fermentation by 30-50%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Apples are the major dietary source of phenolic constituents or antioxidants and the metabolic conversion of these phenolics generates degradation products that has protective effect on cells. Earlier investigations demonstrated that apple juice and their gut fermented products act as effective antioxidant against human colon carcinoma cell line Caco-2 (Bellion et al 2008). It was recognized that the antioxidant activity was higher in peel as compared to the flesh, which was likely due to the high phenolics content in peel (Vieira et al 2011) and also found to inhibit the HepG2 human liver cancer cell proliferation (Wolfe et al 2003).…”
Section: Biological Properties Of Apple Phenolicsmentioning
confidence: 99%
“…Apples are the major dietary source of phenolic constituents or antioxidants and the metabolic conversion of these phenolics generates degradation products that has protective effect on cells. Earlier investigations demonstrated that apple juice and their gut fermented products act as effective antioxidant against human colon carcinoma cell line Caco-2 (Bellion et al 2008). It was recognized that the antioxidant activity was higher in peel as compared to the flesh, which was likely due to the high phenolics content in peel (Vieira et al 2011) and also found to inhibit the HepG2 human liver cancer cell proliferation (Wolfe et al 2003).…”
Section: Biological Properties Of Apple Phenolicsmentioning
confidence: 99%
“…Oxidative stress in cells was quantified using the DCFassay according to Wang and Joseph [21], with slight modifications [12]. Briefly, after incubation with A(P)E/polyphenols, cells were washed and treated for 30 min with dichlorofluorescin-diacetate (final concentration, 50 lM in PBS pH 7.0; 0.5% DMSO v/v), washed and treated with tert-butylhydroperoxide (TBH, 250 lM in PBS) for 30 min at 378C.…”
Section: Cellular Ros-level (Dcf-assay)mentioning
confidence: 99%
“…Phenolic acids, known as intestinal degradation products of above polyphenols [12], were comparatively studied (DMEM + 5% FCS, 24 h incubation). The selected compounds differ in extent of ring hydroxylation and structure of the aliphatic side chain.…”
Section: Peroxide Generation By Individual Apple Juice Phenolics and mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies with colon adenoma and carcinoma cell lines have revealed different potential mechanisms relating to the chemopreventive properties of apple polyphenols. Antioxidant activity of apple polyphenols has been shown in several studies, and this activity could also be demonstrated with reconstituted mixtures of pure compounds [8,9]. Apple polyphenol extracts have also been shown to inhibit proliferation of colon adenoma and colon carcinoma cells, and to induce apoptosis [10,11].…”
Section: Introductionmentioning
confidence: 92%